Insular cortex activity and the evocation of laughter. Issue 8 (2nd September 2015) - Wattendorf, Elise; Westermann, Birgit; Lotze, Martin; Fiedler, Klaus; Celio, Marco R.
ABSTRACT: The insular cortex is fundamentally involved in the processing of interoceptive information. It has been postulated that the integrative monitoring of the bodily responses to environmental stimuli is crucial for the recognition and experience of emotions. Because emotional arousal is known to be closely coupled to functions of the anterior insula, we suspected laughter to be associated primarily with neuronal activity in this region. An anatomically constrained re‐analysis of our imaging data pertaining to ticklish laughter, to inhibited ticklish laughter, and to voluntary laughter revealed regional differences in the levels of neuronal activity in the posterior and mid‐/anterior portions of the insula. Ticklish laughter was associated specifically with right ventral anterior insular activity, which was not detected under the other two conditions. Hence, apparently, only laughter that is evoked as an emotional response bears the signature of autonomic arousal in the insular cortex. J. Comp. Neurol. 524:1608–1615, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Using fMRI the authors reveal a region in the right ventral anterior insular cortex (vaic) that is specific for the production of spontaneous laughter. This finding may suggest that laughter‐related processes are modulated by autonomic efferent signaling from this area.